2019
DOI: 10.1016/j.neulet.2018.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Review of diffusion MRI studies in chronic white matter diseases

Abstract: Diffusion MRI studies characterizing the changes in white matter (WM) due to vascular cognitive impairment, which includes all forms of small vessel disease are reviewed. We reviewed the usefulness of diffusion methods in discriminating the affected WM regions and its relation to cognitive impairment. These studies were categorized based on the diffusion MRI techniques used. The most common method was the diffusion tensor imaging, whereas other methods included diffusion weighted imaging, diffusion kurtosis im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 106 publications
(113 reference statements)
1
33
0
Order By: Relevance
“…Furthermore, the prominent alteration of WM RD over AD showed by FD patients in our sample appears to suggest myelin damage rather than axonal degeneration [ 32 34 ], so that the observed alterations may actually reflect subtle ischemic demyelination of the investigated tracts resulting from vascular pathology [ 35 , 36 ]. Indeed, a similar pattern of DTI metrics alterations is known to characterize both WM hyperintensities (WMH) and normal appearing WM (NAWM) of patients with cerebral small vessel disease (SVD) [ 37 , 38 ]. In particular, several voxel-based DTI studies demonstrated that the occurrence of vascular parkinsonism is associated with more prominent microstructural damage of the bifrontal WM, the corona radiata, and the anterior limb of internal capsule, which are the main tracts involved in movement control [ 39 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the prominent alteration of WM RD over AD showed by FD patients in our sample appears to suggest myelin damage rather than axonal degeneration [ 32 34 ], so that the observed alterations may actually reflect subtle ischemic demyelination of the investigated tracts resulting from vascular pathology [ 35 , 36 ]. Indeed, a similar pattern of DTI metrics alterations is known to characterize both WM hyperintensities (WMH) and normal appearing WM (NAWM) of patients with cerebral small vessel disease (SVD) [ 37 , 38 ]. In particular, several voxel-based DTI studies demonstrated that the occurrence of vascular parkinsonism is associated with more prominent microstructural damage of the bifrontal WM, the corona radiata, and the anterior limb of internal capsule, which are the main tracts involved in movement control [ 39 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the second stage, the remaining signal is then separated into restricted and hindered source of diffusion, modeled as a set of sticks (also known as NDI) and the dispersion of the sticks (also known as ODI), respectively. Restricted (or Gaussian) diffusion occurs when the movement of water molecules is constrained by the presence of impermeable barriers, whereas hindered (or non-Gaussian) diffusion occurs when their movement is constrained by the presence of partially permeable barriers (Martin, 2013;Morozov et al, 2020;Raja, Rosenberg, & Caprihan, 2019). Thus, modeling restricted diffusion as a set of sticks is intended to capture restricted diffusion within neurons and glia (i.e., intracellular diffusion).…”
Section: Diffusion Data Processingmentioning
confidence: 99%
“…Among the MRI signs of CSVD, progressive white matter lesions (T2/FLAIR white matter hyperintensities (WMH)/leukoaraiosis) are the most closely associated with cognitive decline [ 10 ]. Diffusion tensor imaging (DTI) is especially significant in the study of CI due to CSVD [ 6 , 11 , 12 , 13 , 14 ]. DTI, which uses water diffusion to quantitatively measure the state of the brain’s white matter microstructure, has shown significant advantages in characterizing CSVD severity during the evaluation of normal-appearing white matter (NAWH) [ 11 , 12 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Diffusion tensor imaging (DTI) is especially significant in the study of CI due to CSVD [ 6 , 11 , 12 , 13 , 14 ]. DTI, which uses water diffusion to quantitatively measure the state of the brain’s white matter microstructure, has shown significant advantages in characterizing CSVD severity during the evaluation of normal-appearing white matter (NAWH) [ 11 , 12 , 14 ]. The availability of sensitive DTI predictors of CI in CSVD is very important for clinical trials since the slow rate of CI requires treatment efficacy to be evaluated in a very large sample [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation